THE FUTURE OF LANGUAGE TEACHING METHODOLOGY - Ted Rodgers (TEFLIN Journal: A publication on the teaching and learning of English, 1998)
Abstract : This paper reviews the current state of ELT methodology, particulary in respect to a number of current views suggesting that the profession is now in a "post-methods" era in which previous attention to Methods (Total Physical Response, Silent Way, Natural Approach, etc.) has given way to a more generic approach to ELT methodology. Ten potential future courses of ELT methodology are outlines and three of these are considered in some detail. Particular consideration is given as to how past insights from the "methods era" might be incorporated in possible future approaches to ELT methÃÂodology.